Associations Between the Dopamine D4 Receptor Gene Polymorphisms and Personality Traits in Elite Athletes - Michałowska-Sawczyn, Monika; Niewczas, Marta; Król, Paweł; Czarny, Wojciech; Rzeszutko, Agata; Chmielowiec, Krzysztof; Chmielowiec, Jolanta; Grzywacz, Anna; Humińska-Lisowska, Kinga; Lachowicz, Milena; Trybek, Grzegorz; Kaczmarczyk, Mariusz; et al. (Biology of Sport, 2019)
Personality traits and temperament may affect sports performance. Previous studies suggest that dopamine may play an important role in behavior regulation and physical exercise performance. The aim of this study is to determine associations between dopamine D4 receptor gene (DRD4 Ex3) polymorphisms and personality traits (such as neuroticism, extraversion, openness, agreeability and conscientiousness) in elite combat athletes. A total of 302 physically active, unrelated, self-reported Caucasian participants were recruited for this study. The participants consisted of 200 elite male combat athletes and 102 healthy male participants (control group). For personality trait measurements, the NEO Five-Factor Personality Inventory (NEO-FFI) and the State-Trait Anxiety Inventory questionnaires were used. For the genetic assays, blood was collected and all samples were genotyped using the real-time PCR method. A 2 x 3 factorial ANOVA revealed statistically significant differences on the Openness NEO Five Factor Inventory scale for both examined factors, i.e. sport status and genetics DTD4 Ex3. Combat athletes achieved higher scores on the Conscientiousness NEO-FFI scale when compared to controls (7.18 vs 5.98). On the other hand, combat athletes scored lower on the Openness scale in comparison with control group (4.42 vs. 4.63). Subjects with the DRD4 Ex3 s/s genotype had lower results on the openness scale in comparison with participants with the DRD4 Ex3 s/1 genotype (4.01 vs. 4.57) and higher DRD4 Ex3 1/1 genotype (4,01 vs. 3,50). In conclusion, we found an association between the dopamine D4 receptor gene in variable number tandem repeat (VNTR) polymorphisms and athletic status for two NEO-FFI factors: Openness and Conscientiousness. The DRD4 exon 3 polymorphism may be associated with the selected personality traits in combat athletes, thereby modulating athletes’ predisposition to participate in high risk sports.